2018
DOI: 10.1002/jeab.464
|View full text |Cite
|
Sign up to set email alerts
|

Does a rat free a trapped rat due to empathy or for sociality?

Abstract: This report evaluates whether a rat releasing a trapped rat from a restraint tube is better explained as due to its empathic motivation or to the pursuit of social contact. In the first condition, each of six rats chose in an E maze between entering an empty goal box versus entering a goal box where its entrance caused a rat trapped in a restraint tube to be released. Rats preferred the goal box with the trapped rat over the empty goal box. In the second condition, these rats chose between releasing a restrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 14 publications
3
46
0
Order By: Relevance
“…It predicts free rats will prefer the goal box with the rat and the open restraint tubethe very result obtained. Hachiga et al (2018) interpreted these results as consistent with Silberberg et al's (2014) sociality premise. Hiura et al (2018) expanded on the results shown by Silberberg et al (2014) by arranging multiple trials in a session, presenting phases of acquisition and extinction, and varying postsession social restriction.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…It predicts free rats will prefer the goal box with the rat and the open restraint tubethe very result obtained. Hachiga et al (2018) interpreted these results as consistent with Silberberg et al's (2014) sociality premise. Hiura et al (2018) expanded on the results shown by Silberberg et al (2014) by arranging multiple trials in a session, presenting phases of acquisition and extinction, and varying postsession social restriction.…”
supporting
confidence: 69%
“…There are two reasons for this perspective. First, for Silberberg et al (2014) and Hachiga et al (2018), a sociality account consistently succeeds in accommodating outcomes whereas an empathy account does not. Thus, in terms of parsimony, a sociality account seems favored.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies of pro-social behavior in rats have also demonstrated that rats are able to release a trapped rat from a restraint tube (Ben-Ami Bartal et al, 2011;Hachiga et al, 2018). Similarly, mothers develop a preference for a compartment previously associated with pups (Fleming et al, 1994;Panksepp and Lahvis, 2007) and lever press to gain access to pups (Hauser and Gandelman, 1985) (Lee et al, 2000).…”
Section: Social Interactions Are Rewarding and Can Overcome Drug Rewardmentioning
confidence: 99%
“…However, in these observation systems, it remains unclear whether the observer mouse truly recognises the movements of and empathises with the demonstrator mouse. Given that even humans cannot know exactly what others feel and think, it is necessary to exercise caution when discussing whether mice and rats have an ability to empathise [34][35][36].…”
Section: Introductionmentioning
confidence: 99%